Effect of In-trough and Out-of-trough fixturing in vibro-polishing - Yuvaraj, Hemanth Kumar (2023)
Advanced compressor design with superior aerodynamic and fatigue life performance demands superior surface quality, typically Ra≤0.25 µm. Vibro-polishing is media finishing technology which is commonly employed to mass finish aerospace engine components such as blisks. Frequency of vibration, location, and orientation of workpiece, media size, lubrication etc. are known tuneable knobs to optimize the performance of Vibro-polishing. However, longer cycle times in vibro-polishing still pose a challenge. In this study, effect of In-trough (IT) and Out of trough (OOT) fixturing at various depths of immersion into the media is studied. Workpiece used was made of Ti-6Al-4V with a geometry representative of a blisk blade. OOT fixturing was observed to yield better surface quality than IT fixturing irrespective of the depth of immersion. Further, a very low Ra of about 0.10 µm was achieved with 1 h of processing at highest depth of immersion into the media in OOT fixturing, resulting in significant reduction in cycle time to reach aerospace component surface roughness of Ra≤0.25 µm. Further, uniform vibro-polished surface topography with no alterations in the as received microstructure was observed in both IT and OOT fixturing.